Left atrial mechanical dyssynchrony: an independent predictor of left ventricular reverse remodelling after cardiac resynchronization therapy. (4th February 2022) - Hammersboen, LER; Aalen, JM; Puvrez, A; Remme, EW; Donal, E; Duchenne, J; Voigt, JU; Galli, E; Khan, FH; Sletten, OJ; Smiseth, OA; Stugaard, M
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Institute for Chirurgical Research - Oslo University Hospital Introduction: Left bundle branch block (LBBB) leads to left ventricular (LV) mechanical dyssynchrony. Since the left atrium (LA) and the left ventricle (LV) are anatomically connected, dyssynchronous LV contractions may be transmitted to the LA causing LA dyssynchrony and disturbed LA function. Purpose: To investigate if LA dyssynchrony induced by LBBB predicts LV reverse remodelling after cardiac resynchronization therapy (CRT). Methods: In a prospective study, myocardial strain was measured by speckle-tracking echocardiography in 171 heart failure patients with LBBB, before and 6 months after CRT. LA dyssynchrony was measured as the time delay between onset systolic stretch of the interatrial septum and the LA lateral wall (white arrows in Figure), and LV dyssynchrony as the time from onset septal shortening to onset lateral wall shortening. Septal flash was assessed visually. Response to CRT was defined as at least 15 % reduction in LV end systolic volume at 6 months follow up. Results: The figure shows a representative LBBB patient with LA and LV dyssynchrony which was abolished by CRT. For the whole study population, LA dyssynchrony was 104 ± 77 ms (mean ± SD) before CRT, and decreased to 43 ± 70 ms (p < 0.0001) after CRT. There was a significant correlation between LA and LV dyssynchrony (r = 0.68, p < 0.0001). LA dyssynchrony correlated with LV reverse remodelling after CRT (p = 0.009), and multivariable analysis revealed that LA dyssynchrony was an independent predictor of CRT response (β=-0.046, p = 0.04) when combined with septal flash, QRS duration and QRS morphology (Table). Conclusions: Patients with LBBB had marked LA dyssynchrony which was attributed to direct LV-LA mechanical interaction. Furthermore, LA dyssynchrony was an independent predictor of LV reverse remodelling after CRT. These findings suggest that assessment of LA dyssynchrony should be part of the echocardiographic evaluation in patients with dyssynchronous heart failure.